Enhancements of Optoelectronic Properties of Doped CsSnCl3 for Next-Generation Devices (Bangladesh Journal of Physics, 2024)
In advanced electrical and photovoltaic applications, inorganic metal halide perovskite materials have become strong contenders because of their remarkable properties. However, the pure form of cesium tin chloride exhibits suboptimal electro-optical capabilities, hindering its potential for achieving ideal optoelectronic efficiency. This study employs density functional theory to compute and analyze the structural, elastic, electrical, and optical properties of both pure CsSnCl3 and its doped variants with Ti, V, Cr, Mn, Sb, In, Fe, Cu, and Zn at various concentrations. By maintaining consistent computational parameters, we explored the electrical and optical attributes of these materials and their respective ground states, aiming to identify the most promising doped phase of CsSnCl3 for high-performance optoelectronic applications. Our findings not only highlight the potential of doped perovskite materials but also provide valuable insights for researchers and industry professionals in selecting the optimal doped phase of CsSnCl3, paving the way for significant advancements in optoelectronics.Bangladesh Journal of Physics, Vol. 31, Issue 1, pp. 1–16, June 2024